The mythos of laudable pus along with an explanation for its origin - Jeffrey A. Freiberg (Greater Baltimore Medical Center, 2017)
The presence of pus is one of the most easily recognizable signs of an infection. However, for several centuries suppuration, known as 'laudable pus,' was believed to be a sign of a healthy, healing wound. This historical misconception can be explained by the difference in the presentation of a necrotizing soft tissue infection versus other more common skin and soft tissue infections. Chronic wound infections, due to pyogenic bacteria, typically produce large amounts of thick, whitish-yellow pus. On the other hand, necrotizing soft tissue infections, despite their severe mortality and morbidity, are devoid of pus in the traditional sense. What the ancient medical observers recognized was the fact that pus is not characteristic of this subset of incredibly severe infections. This is an important distinction to remember when evaluating an infection, even today.